Glacial Discharge and its Impact on Phytoplankton Taxonomic Composition in an Antarctic Fjord - Jack Pan, B. (2020)
The influence of glacial discharge on phytoplankton community composition remains an open question. The Antarctic Peninsula fjords offer an ideal system to understand the effect of ice-ocean forcing on phytoplankton community, providing an extreme in the spatial gradient from the glacio-marine boundary to the Western Antarctic Peninsula (WAP) continental shelf. In Andvord Bay, we found that glacial meltwater input altered surface salinity and was enriched in dissolved iron and nitrate, supporting phytoplankton biomass. The three major groups of phytoplankton fueled by glacial input were: cryptophytes, diatoms, and a group of unidentified small flagellates. In December, cryptophytes dominated the phytoplankton community and were correlated with relatively warmer temperatures in the surface layer; in addition, contrary to our hypothesis, no diatom bloom was observed in the fjord in spite of dissolved iron concentration >1 nM. By April, after the growth season, the overall phytoplankton abundance had decreased by an order of magnitude. Phytoplankton, in particular diatoms, were then limited by daytime length despite abundant macro-nutrient and iron concentrations. Mixed flagellates emerged as the dominant group during April due to the decline of other major taxa. Deep-learning algorithms for predicting the abundance of each major phytoplankton group captured the effects of these environmental factors on the phytoplankton community. Our results show that the fjord, under the influence of glacial meltwater, has relatively high phytoplankton biomass combined with high macro- and trace nutrient concentrations when compared to other WAP regions influenced by sea ice melting. Based on this study, we confirm that flagellates can be the dominant taxon in Antarctic fjords and we propose that iron concentration alone is insufficient to predict diatom growth. Furthermore, buoyant meltwater plumes can enrich the fjord with nitrate even if the main circulation is not driven by glacier meltwater discharge. As glacial meltwater continues to alter the phytoplankton taxonomic composition, it will have an important implication for higher trophic levels and add significant uncertainties to the prediction of regional ecosystem dynamics and biogeochemistry.